STUDI ETNOSAINS: REKONSTRUKSI PROSES PEMBUATAN KERUPUK BANGRENG MENJADI MATERI PEMBELAJARAN IPAS SD - Elvira Santika Yuliandini; Pera Siti Padilah; Poppy Anggraeni; Encep Iman Hadi Sunarya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Ethnoscience is knowledge possessed by a community that can be reconstructed into scientific knowledge based on cultural and local knowledge systems regarding natural phenomena. This study aims to reconstruct local community knowledge into scientific knowledge concerning the production of Bangreng crackers in Cijeler Village, Sumedang. The research employs a qualitative descriptive method, with data collected through participatory observation, in-depth interviews with local artisans, and literature studies. The results indicate that traditional processes such as nyampur biang (dough preparation), the use of luweng (traditional stoves), and disoé (drying) possess strong scientific foundations, encompassing principles of starch gelatinization, heat transfer through convection, radiation, and evaporation. This ethnoscience reconstruction serves as a bridge to transform abstract scientific concepts into concrete learning materials for elementary school students. The findings suggest that integrating local wisdom into the school curriculum can significantly enhance students' scientific literacy by connecting classroom theory with everyday cultural practices.